Does Financial Literacy Have A Role on Financial Behavior in The Digital Context? - Adam Nurkholik (Universitas 45 Surabaya, 2024)
The digital financial behavior of millennials is still messy and unstable. This quantitative study aims to analyze the effect of digital financial literacy on millennials' digital financial behavior. Data was collected by distributing online questionnaires to four hundred and twenty millennials in Jabodetabek as the research sample. The determination of the research sample is based on the calculation of Slovin's formula with purposive sampling technique. Recapitulation of respondent answer data is automatically stored on Google Drive. Data analysis utilizes free R Studio software with descriptive statistics to compile respondent demographics and PLS-SEM calculations. The findings of this study indicate that digital financial literacy has a significant positive influence on digital financial behavior. This means that a good understanding of digital financial products in the digitalization era will create wise digital financial management behavior for millennials. Following up on these findings, millennials must fix their digital financial behavior as a solution to success through mastering digital financial literacy because they face uncertainty that must be counteracted with the principles of priority scale and prudence.